Demographic, health-related, and work-related factors associated with body mass index and body fat percentage among workers at six Connecticut manufacturing companies across different age groups: a cohort study. Issue 1 (December 2015) - Garza, Jennifer; Dugan, Alicia; Faghri, Pouran; Gorin, Amy; Huedo-Medina, Tania; Kenny, Anne; Cherniack, Martin; Cavallari, Jennifer
Abstract Background Effective workplace interventions that consider the multifactorial nature of obesity are needed to reduce and prevent obesity among adults. Furthermore, the factors associated with obesity may differ for workers across age groups. Therefore, the objective of this study was to identify demographic, health-related, and work-related factors associated with baseline and changes in body mass index (BMI) and body fat percentage (BFP) and among Connecticut manufacturing workers acrossage groups. Methods BMI and BFPof 758 workers from six Connecticut manufacturing companies were objectively measuredat two time points approximately 36 months apart. Demographic, health-related, and work-related factors wereassessed via questionnaire. All variables were included in linear regression models to identify factors associated with baseline and changes in BMI and BFP for workers in 3 age groups: <45 years (35 %), 45–55 years (37 %), >55 years (28 %). Results There were differences in baseline and changes in BMI and BFP among manufacturing workers across age groups. Being interested in changing weight was significantly (p < 0.01) associated with higher baseline BMI and BFP across all age categories. Other factors associated with higher baseline BMI and BFP differed by age group and included: male gender (BMIp = 0.04), female gender (BFP p < 0.01), not having a college education (BMIp = 0.01, BFPp = 0.04), having childcare responsibilities (BMIp = 0.04), and working less overtime (p = 0.02) among workers in the <45 year age category, male gender (BMIp = 0.02), female gender (BFPp < 0.01) and reporting higher stress in general (BMIp = 0.04) among workers in the 45–55 year age category, and female gender (BFPp < 0.01) and job tenure (BFPp = 0.03) among workers in the >55 year age category. Few factors were associated with change in BMI or BFP across any age category. Conclusions Among manufacturing workers, we identified associations between individual, health-related, and work-related factors and baseline BMIand BFP that differed by age. Such results support the use of strategies tailored to the challenges faced by workers in specific age groups rather than adopting a one size fits all approach. Effective interventions should consider a full range of individual, health-related, and work-related factors. More work must be done to identify factors or strategies associated with changes in obesity over time.